SOSIALISASI TERAPI MENIUP BALING-BALING TERHADAP SKALA NYERI SAAT DILAKUKAN TINDAKAN INVASIF (INJEKSI) PADA ANAK USIA PRASEKOLAH (3-6 TAHUN) DIRUANG KEMUNING RSUD BAYU ASIH PURWAKARTA - Wirdan Fauzi Rahman; Serly, Serly; Tabitha Amelia (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Pain is an unpleasant experience that often causes fear and anxiety in children, especially during invasive procedures such as injections. One non-pharmacological intervention to reduce pain is the pinwheel blowing therapy, which serves as a distraction by shifting the child’s focus to a pleasant activity. Objective: To determine the effect of pinwheel blowing therapy on pain scale during injection procedures among preschool-aged children (3–6 years old) in Kemuning Ward, Bayu Asih Hospital, Purwakarta. This study used a quasi-experimental design with a one-group pretest–posttest design.. Pain level was measured using the Wong-Baker Faces Pain Rating Scale. Data were analyzed using the Wilcoxon Signed Rank Test. Results: The mean pain score before the intervention was 5.9, which decreased to 2.3 after the pinwheel blowing therapy. Conclusion: Pinwheel blowing therapy was effective in reducing pain intensity during injection procedures among preschool-aged children. This therapy can be applied as a simple, safe, and enjoyable non-pharmacological nursing intervention to minimize procedural pain in children